2020
DOI: 10.3390/agronomy10070927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gibberellin Responsive Reduced Height Allele Rht13 on Agronomic Traits in Spring Bread Wheat in Field Experiment in Non-Black Soil Zone

Abstract: The introduction of gibberellin-responsive reduced height (GAR Rht) alleles is a promising tool for breeding semi-dwarf, high-input varieties of wheat. We have compared recombinant isogenic lines F2:3 carrying dwarfing allele Rht13 and without dwarfing alleles, obtained from the cross of isogenic lines and selected from F2 using molecular markers. After phenotyping and statistical analysis, we found that the Rht13 allele reduces total plant height by 13.0 cm (17.4%), while the proportions between the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In order to understand the effect of the GA-sensitive dwarfing gene F 1 , crosses were developed having Rht13 genes by crossing different parental lines. It was observed that the genotypes having Rht13 showed a significant reduction in the plant height, lodging and increased yield, agreeing with the findings of Divashuk [ 20 ]. Contrary to that, it was also observed that GA-sensitive gene Rht18 reduced plant height (−24%) and lodging (−51%) compared to the wild-type tall plants.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In order to understand the effect of the GA-sensitive dwarfing gene F 1 , crosses were developed having Rht13 genes by crossing different parental lines. It was observed that the genotypes having Rht13 showed a significant reduction in the plant height, lodging and increased yield, agreeing with the findings of Divashuk [ 20 ]. Contrary to that, it was also observed that GA-sensitive gene Rht18 reduced plant height (−24%) and lodging (−51%) compared to the wild-type tall plants.…”
Section: Discussionsupporting
confidence: 88%
“…The hybrids, along with their parents, were sown in three replications under RCBD under normal (03 irrigations) and drought stress (01 irrigation); each irrigation was 120 mm. The data were recorded for days to heading (days) from sowing to 50% of heading, lodging (%) calculated by the formula (Lodging% = %plot area lodged × angle of lodging/90) [ 20 ], at physiological maturity plant height (cm), peduncle length (cm), internodal length (cm), stem diameter (mm) was calculated by vernier caliper from top, middle and bottom, then the average value of the stem diameter was calculated, days to maturity (days) was recorded from days from germination to the days to physiological maturity, spike length (cm), number of grains/spike, 1000-grain weight (g), grain yield/plant (g), chlorophyll contents (mg/g dry weight) were recorded from the base, the mid and upper part of the flag leaf with the SPAD 502 Plus Chlorophyll Meter (Spectrum Technologies Inc., Aurora, IL, USA) and then average value for chlorophyll contents was calculated. The stomatal conductance was estimated by using CIRAS-3 Portable CO 2 /H 2 O Gas Analysis System, PP Systems, Amesbury, MA, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Australian varieties Espada and Gregory were both represented with GAS Rht13 and Rht18 dwarfing gene NILs, with Rht13 reducing height to a greater extent than Rht18 . A strong height-reducing effect for Rht13 was also reported by Divashuk et al (2020) and Rebetzke et al (2011) . Notwithstanding, the extent of height reduction with Rht13 was contingent on genetic background (cf.…”
Section: Discussionsupporting
confidence: 67%
“…Rht13 is another promising alternative dwarfing gene that reduces final plant height without affecting seedling growth (Ellis et al, 2004;Rebetzke et al, 2011). The dwarfing allele Rht-B13b produced a strong height reduction between 17 % and 34 % compared to Rht-B13a, which is comparable to reductions typical of Rht-B1b and Rht-D1b, depending on the genetic background and growing conditions (Rebetzke et al, 2011;Rebetzke et al, 2012;Wang, Y et al, 2014;Wang et al, 2015;Divashuk et al, 2020). Genetic mapping located Rht13 on the long arm of chromosome 7B (Ellis et al, 2005) but the underlying gene has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%